1990
DOI: 10.1128/iai.58.8.2502-2509.1990
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of granulocyte colony-stimulating factor alone and in combination with antibiotics against Pseudomonas aeruginosa infections in mice

Abstract: The therapeutic efficacy of granulocyte colony-stimulating factor (G-CSF) against an experimental intramuscular infection induced by Pseudomonas aeruginosa in mice was confirmed. Bacterial growth in the infected thigh muscle was suppressed by G-CSF treatment. The change in the number of peripheral blood polymorphonuclear leukocytes (PMN) after bacterial challenge was investigated. The results showed that G-CSF could stimulate stronger defense mechanisms after stimulation by bacterial challenge. In the G-CSF-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…Our results, obtained in a prophylaxis model, as well as the favourable results reported by others in therapeutic intervention models [15,16], justify further studies on the role of G-CSF treatment in non-neutropenic infections. Of interest, a recent paper reported protection in a rat pneumococcal pneumonia model following therapeutic but not prophylactic administration of human G-CSF [17].…”
Section: Discussionsupporting
confidence: 85%
“…Our results, obtained in a prophylaxis model, as well as the favourable results reported by others in therapeutic intervention models [15,16], justify further studies on the role of G-CSF treatment in non-neutropenic infections. Of interest, a recent paper reported protection in a rat pneumococcal pneumonia model following therapeutic but not prophylactic administration of human G-CSF [17].…”
Section: Discussionsupporting
confidence: 85%
“…In this report, we showed that LSN B, a new CSF inducer derived from S. platensis, has a strong activity in protecting hosts against infection with E. coli. At first, we expected that LSN B induced G-or GM-CSF in vivo and thereby enhanced host resistance by stimulating bactericidal activity of neutrophils because these cytokines are reported to enhance the host resistance against several infections (2,(14)(15)(16)(17)22). However, we could not detect the induction of GM-CSF in vivo.…”
Section: Discussionmentioning
confidence: 75%
“…G-CSF and GM-CSF are reported to enhance resistance against several infections in normal and immunosuppressed hosts in experimental models (2,(14)(15)(16)(17)22). These cytokines also enhance the Fig.…”
mentioning
confidence: 99%
“…15,16,20 The main finding was that a combination of G-CSF and IFN-␥ as an adjunct to vancomycin resulted in no improvement in antienterococcal treatment outcome compared with adjunctive therapy with only G-CSF. Although copious literature describes the beneficial effect of G-CSF or IFN-␥ in enhancing antibiotic therapy in animal infection models as well as in humans, [24][25][26][27][28][29] information regarding an adjunctive combination of cytokines in treating infections is sparse. Given reports of combination G-CSF-and IFN-␥induced additive in vitro antimicrobial activity, 30,31 it was reasoned that it is possible that such an interaction may be seen against enterococci.…”
Section: Discussionmentioning
confidence: 99%